Studi Komunitas Bakteri Hidrolitik Saluran Pencernaan Ikan Nilem (Osteochilus vittatus) yang Dibudidayakan Di Kabupaten Banyumas - Emyliana listiowati; Anandita Ekasanti; Dewi Nugrayani; Hamdan Syakuri; Dewi Wisudyanti; Muhammad Nurhafid; Yohanes Evander (Universitas Batangahari Jambi, 2022)
Hydrolytic bacteria are bacteria that play an important role in helping the digestive process of fish. This study aims to determine the hydrolytic activity of bacteria in the digestive tract of Nilem fish seen from amylolytic, proteolytic, lipolytic and cellulitic indices. The method used is exploratory and data analysis using parametric and non-parametric to explain the research data. Exploration carried out in this study included the total number of bacteria, proportion of hydrolytic bacteria, activity index of hydrolytic bacteria and molecular identification of bacteria with the best activity index. Fish were taken at random from fish farming ponds in Beji and Singasari with three fish each. The number of bacteria found an increasing pattern to the posterior intestine of fish from Beji and a pattern that varied between parts of the intestine of fish from Singasari. Hydrolytic bacteria were isolated from each part of the intestine from both locations which showed a decreasing pattern in each type of hydrolytic and intestinal tracts of fish from Singasari and varied patterns in the intestines of fish from Beji. The hydrolytic activity index showed a stable average value in each part of the intestine and the sampling location. Based on the best activity index, seven isolates were identified from three different genera, namely 1) Bacillus subtilis, 2) Enterobacter mori, Enterobacter cloacae, and 3) Aeromonas hydrophila (3), Aeromonas veronii. The bacteria obtained are classified as non-pathogenic bacteria that have potential in the field of aquaculture and normal pathogenic bacteria in the fish intestine